On the Picture Fuzzy-TOPSIS Method (European Journal of Pure and Applied Mathematics, 2024)
Research related to the Technique for Order Preference by Similarity to Ideal Solotion (TOPSIS) method have been developed using fuzzy or intuitionistic fuzzy sets. In this article, we provide the development of the topsis method based on the generalization of fuzzy sets. We present a new method of topsis based on picture fuzzy sets. In this article, we propose steps of TOPSIS picture fuzzy sets method. Finally, we presented the illustrative example of this method.
Keywords: TOPSIS; Picture Fuzzy Sets